CONTINUITIES AND BREAKS AROUND SOCIAL JUSTICE DURING THE FIRST PERONISM IN SANTIAGO DEL ESTERO (1943-1955) - Erbetta, María Cecilia (Revista de Historia Social y de las Mentalidades, 2011)
In this paper we propose to analyze the Peronism in the province of Santiago del Estero from a look that tries to uncover the way in which the spaces provincial and national interlaced between 1943 and 1955, and to place its particularity among old and new. In other words, we believe that the political space santiagueño, hegemonized by Peronism almost from its irruption as such, has a dynamic in which the spatial boundaries between national and provincial level, and temporal, between past and present, are re-meant and rewrite in a permanent way around the Social Justice. The principal aim is realize of the scopes that had the work justice across the functioning of public organisms (office, department, delegation and Work Courts) in relation, in turn, with other institutions from which there is revealed the principles of social justice as the Peronism conceives them during this period.